2008
DOI: 10.1007/s10158-008-0067-5
|View full text |Cite
|
Sign up to set email alerts
|

The identification and distribution of gonadotropin-releasing hormone-like peptides in the central nervous system and ovary of the giant freshwater prawn, Macrobrachium rosenbergii

Abstract: In the present study, we demonstrated the existence of GnRH-like peptides in the central nervous system (CNS) and ovary of the giant freshwater prawn, Macrobrachium rosenbergii using immunocytochemistry. The immunoreactivity (ir) of lamprey (l) GnRH-III was detected in the soma of medium-sized neurons located in neuronal cluster number 11 in the middle part of supraesophageal ganglion (deutocerebrum), whereas ir-octopus (oct) GnRH was observed in the soma of both medium-sized and large-sized neurons in thoraci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 48 publications
(71 reference statements)
3
29
1
Order By: Relevance
“…Similarly, in our earlier studies, lamprey (I) GnRH-ir and octGnRH-ir have not been detected in the eyestalk of P. monodon (Ngernsoungnern et al 2008c) or in M. rosenbergii (Ngernsoungnern et al 2008a). This is in contrast to the report by Amano et al (2009) who have shown GnRH-ir in the neurons of the medulla interna and immunoreactive fibers in the medulla interna, medulla externa, and lamina ganglionalis in the Kuruma prawn, Marsupenaeus japonicus.…”
Section: Discussioncontrasting
confidence: 81%
See 4 more Smart Citations
“…Similarly, in our earlier studies, lamprey (I) GnRH-ir and octGnRH-ir have not been detected in the eyestalk of P. monodon (Ngernsoungnern et al 2008c) or in M. rosenbergii (Ngernsoungnern et al 2008a). This is in contrast to the report by Amano et al (2009) who have shown GnRH-ir in the neurons of the medulla interna and immunoreactive fibers in the medulla interna, medulla externa, and lamina ganglionalis in the Kuruma prawn, Marsupenaeus japonicus.…”
Section: Discussioncontrasting
confidence: 81%
“…Furthermore, no octGnRH-ir has been detected in neurons or in any neuropils in the abdominal ganglia of M. rosenbergii (Ngernsoungnern et al 2008a), although some positive fibers have been seen in P. monodon (Ngernsoungnern et al 2008c). Since the intensity of GnRH-ir is low, and since positive fibers are sparse, we suggest that GnRH in the abdominal ganglia might not be a significant factor in the regulation of ovarian maturation in the white shrimp.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations